Investigating the Effect of Financial Literacy on Financial Decision-Making of Prospective Teachers in Universities of South Punjab - Zartaj Jamil; Dr. Farah Deeba (Indus Journal of Social Sciences, 2025)
Numerous studies have reported the importance of financial literacy and financial decision making for students of business administration field and its impact on their professional success. However, little is known about the role of financial literacy upon the financial decision-making of prospective teachers in the field of teacher education. This study aimed to ascertain the effect of financial literacy on financial decision-making skills of prospective teachers. Data were collected from 219 out of 847 prospective teachers (students enrolled in B.Ed. (Hons) and BS programs three public sector universities of Multan. Two scales (Financial Literacy Scale=32 items) and (Financial Decision-making Skills Scale =6 items) were used for data collection. The scales were pilot tested before using in the study context for data collection. The Cronbach’s alpha values for both the scales were above.70 which was at acceptable level. Linear regression was used to analyze the collected data. The regression analysis showed that there was a positive effect of financial literacy and its two components: financial behaviour and financial attitude on financial decision-making of prospective teachers. Based on these findings it is argued that financial literacy improves students’ attitude and behaviour towards financial decision-making skills. It is suggested that these results may be tested in other context for further understanding of the correlation between these variables.